Transcriptome dynamics of Camellia sinensis in response to continuous salinity and drought stress - Zhang, Qing; Cai, Muchen; Yu, Xiaomin; Wang, Lishan; Guo, Chunfang; Ming, Ray; Zhang, Jisen (Tree genetics & genomes, 2017)
Camellia sinensis is an important economic crop worldwide since this plant is used to make one of the most popular non-alcoholic beverages, tea. Salinity together with drought pose a serious threat to the production and qualities of C. sinensis . However, the transcriptome dynamics occurring in response to drought stress and salt stress in tea plants are poorly understood at the molecular level. We reported the first large-coverage transcriptome datasets for C. sinensis under drought and salt stress using next-generation sequencing technology. Using a high-throughput Illumina sequencing platform, approximately 398.95 million high-quality paired-end reads were generated from young leaves of C. sinensis subjected to drought stress and salt stress, and these reads were used for de novo assembly. The transcripts with further processing and filtering yielded a set of 64,905 coding DNA sequences (CDSs) with an average length of 710 bp and an N50 of 933 bp. In total, 3936 and 3715 differentially expressed genes (DEGs) were identified from all analyzed time points of drought stress and salt stress, respectively. Identified in drought and salt stress were 2131 overlapping DEGs, and these are involved in galactosyltransferase activity, tetrapyrrole binding, and hydrolase activity, indicating that C. sinensis has a similar molecular response to these two stresses . We clustered the above DEGs from both sets into four clusters according to their expression dynamics, with the genes in each cluster showing enrichment for particular functional categories. We also found that under salt stress, most DEGs showed down-regulation at early time points and their expression levels were elevated after 48 h, whereas under drought stress most DEGs were down-regulated in all time points. The DEGs relative to pathways of osmotic product such as proline, sugar, and GABA were identified in C. sinensis . Noteworthy, among the identified DEGs are genes involved in the biosynthetic pathways of polyphenol and caffeine, providing evidence at the molecular level that salt and drought affect tea qualities. In addition, we analyzed the differential expression of transcription factors and revealed a large amount of crosstalk between the metabolic pathways of drought and salt stress. All findings suggest that gene expression exhibits rapid and coordinated changes during C. sinensis adaptations to drought stress and salt stress, and common themes in the response to both stresses were identified.